Analysis of sport supplement consumption by competitive swimmers according to sex and competitive level - Moreno, B.; Veiga, S.; Sanchez-Oliver; Sánchez-Oliver, A. J.; Domínguez, R.; Morencos, E. (Nutrients, 2022)
Sports supplements (SS) are commonly used by athletes to improve their performance. SS use by competitive swimmers is reported to be prevalent but there is no evidence of such use by elite swimmers, either male or female. The objective of this research was to study the patterns of SS use by competitive swimmers based on sex and competitive levels (national and international); Methods: Using the categories of the Australian Institute of Sport (AIS), a total of 102 competitive swimmers (59 men and 43 women) completed a validated self-administered questionnaire on the use of SS; (3) Results: Overall, 86.9% of swimmers had consumed SSs with no differences observed between males and females (p = 0.247) or between competitive levels (p = 0.597). The SS that were most consumed by swimmers were caffeine (53.5%), sport drinks (52.5%), sport bars (51.5%), and vitamin C (43.4%). SSs categorized as medical supplements were consumed significantly more frequently by international swimmers (p = 0.012), with significant differences also found in the level—sex interaction (p = 0.049); (4) Conclusions: Compared to other sports disciplines, the prevalence of SS consumption is high in competitive swimmers regardless of performance level or gender. However, the consumption of medical supplements was greater in swimmers at a higher performance level.